(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Child sexual abuse (CSA) is a pressing global concern with far-reaching psychological, emotional, and social implications for survivors. A proactive, multi-dimensional strategy is essential to increase awareness and implement prevention measures, focusing on family involvement, school-based education, and media influence. This study explores the effectiveness of parental guidance, school interventions, and media campaigns in raising awareness and mitigating CSA risks. Drawing from recent research, statistical reports, and case studies, this paper identifies key barriers to CSA prevention and offers practical recommendations to enhance protective measures. It underscores the collective responsibility of society in safeguarding children from abuse.